Cch1p mediates Ca2+ influx to protect Saccharomyces cerevisiae against eugenol toxicity. - Stephen K Roberts (Public Library of Science (PLoS), 2012)
Eugenol has antifungal activity and is recognised as having therapeutic potential. However, little is known of the cellular basis of its antifungal activity and a better understanding of eugenol tolerance should lead to better exploitation of eugenol in antifungal therapies. The model yeast, Saccharomyces cerevisiae, expressing apoaequorin was used to show that eugenol induces cytosolic Ca(2+) elevations. We investigated the eugenol Ca(2+) signature in further detail and show that exponentially growing cells exhibit Ca(2+) elevation resulting exclusively from the influx of Ca(2+) across the plasma membrane whereas in stationary growth phase cells Ca(2+) influx from intracellular and extracellular sources contribute to the eugenol-induced Ca(2+) elevation. Ca(2+) channel deletion yeast mutants were used to identify the pathways mediating Ca(2+) influx; intracellular Ca(2+) release was mediated by the vacuolar Ca(2+) channel, Yvc1p, whereas the Ca(2+) influx across the plasma membrane could be resolved into Cch1p-dependent and Cch1p-independent pathways. We show that the growth of yeast devoid the plasma membrane Ca(2+) channel, Cch1p, was hypersensitive to eugenol and that this correlated with reduced Ca(2+) elevations. Taken together, these results indicate that a cch1p-mediated Ca(2+) influx is part of an intracellular signal which protects against eugenol toxicity. This study provides fresh insight into the mechanisms employed by fungi to tolerate eugenol toxicity which should lead to better exploitation of eugenol in antifungal therapies.